Household Income Differences between Residential Distance from the Toll Road in Indonesian Suburban Areas - Tiara Ariyanda; Khoirunurrofik Khoirunurrofik (Department of Urban and Regional Planning, Universitas Diponegoro, 2020)
Toll roads play a significant role in regional development. Moreover, toll roads affect the behavioral patterns of the people who reside in the surrounding areas and the region's development. Toll roads improve accessibility to resources that lead to higher productivity and ultimately foster economic growth. This paper aims to examine the difference in household income levels between suburban areas before the construction of Bakauheni–Terbanggi Besar toll road in 2014 and after the toll road construction in 2017. Toll road construction is associated with society's income; the areas closer to the toll road are inclined to have higher income levels. Furthermore, the construction of a toll road creates socio-economic opportunities and improves accessibility for society. This research used an income effect model to develop transformational household changes using the Ordinary Least Square (OLS) Regression. It is discovered that there is a behavioral correlation both in and between the households that leads to shifts in the work sector, income level, health, and education. This research showed that households' income is significantly increased after toll construction. Residential distance from toll also has a strong correlation with income, which households residing closer to the toll road have earned more income than those residing farther.